Pengaruh Persepsi Harga, Kualitas Produk Dan Promotion Terhadap Minat Beli Konsumen Untuk Membeli Produk Fashion Premium iROO Melalui Online shop Dengan Brand Awareness Dan Persepsi Nilai Sebagai Variabel Mediasi - Farida Rusila; Triyono Arief Wahyudi (STREAMING, 2025)
Rapid growth market share e-commerce or online shop in indonesia were no longer can doubt.With of internet users is the 82 million people or about 30 percent of the population in indonesia, e-commerce market a gold mine who its desire for some of us can see the potential to depannya.iroo-indonesia.com is one of shopping online that working in the area of retail fashion special woman who has market share pretty good since starting the retail business in indonesia. This Research aims to understand ( 1 ) the influence perception price to the wishes of to buy fashion premium iroo through online shop with the brand awareness and presepsi the value as variable mediation ( 2 ) the influence quality of product against desire to purchase fashion premium iroo through online shop with the brand awareness and perception the value as variable mediation ( 3 ) the influence promotion to the wishes of to buy fashion premium iroo through online shop with the brand awareness and presepsi the value as variable mediation.Respondents in this research was customer that has become members and have done the purchase of online, with the number of sample as many as 180 respondents. The Method of this research is description. Technique data analysis in this research was analysis a path or ( path analisys ) by using linear regression multiple .The research results show that the size of the contributions influence perception of prices ( x1 ) , the quality of product ( x2 and promotion ( x3 ) impact of 60.6 % of consumer advocacy to buy through perception the value of ( meters , while the rest of 39.4 % influenced by another factor.